DIVERSITY OF MEDICINAL PLANTS IN ERATTI HILL, THAMARAIKARAI BEAT OF BARGUR RESERVE FOREST, WESTERN GHATS IN ERODE DISTRICT, TAMILNADU, INDIA - P, Vijayashalini; P, Abirami (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study was planned to document the medicinal plants in Eratti hill. Methods: The medicinal plants were collected during their flowering period from July to September. Voucher specimens of all medicinally valuable plants were collected, poisoned, dried, and mounted with voucher number following the conventional methods. Results: Survey of medicinal plants wealth of Eratti hill, Bargur reserve forest, Western Ghats of Tamil Nadu, India, was carried out during 2016– 2018. 295 medicinal plant species belonging to 66 families were documented. Of these, the highest number of species belongs to the families were Asteraceae, Acanthaceae, Euphorbiaceae, Fabaceae, Convolvulaceae, Solanaceae, Amaranthaceae, Lamiaceae, Asclepiadaceae, Malvaceae, Mimosaceae, and Apocynaceae. Herbs held the dominant position followed by shrubs, trees, climbers, and epiphytes. The medicinal plants were used to treat various ailments such as skin diseases, rheumatoid arthritis, asthma, fever, colic pain, biliousness, wounds eczema, cardiac disorders, and eye diseases used by the Solagars, Lingayats, and Malayali tribals in the hill. Conclusion: Medicinal plants in Eratti hill play a significant role in primary health care of the ethnic people. This study provides knowledge about herbal treatment of the ethnic people and subsequent pharmacognostical and pharmacological investigations should be made to confirm their mode of preparations.